2009
DOI: 10.1074/jbc.m809687200
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of Superoxide Dismutase (SOD1) in Human Erythrocytes

Abstract: Over 100 mutations in Cu/Zn-superoxide dismutase (SOD1) result in familial amyotrophic lateral sclerosis. Dimer dissociation is the first step in SOD1 aggregation, and studies suggest nearly every amino acid residue in SOD1 is dynamically connected to the dimer interface. Post-translational modifications of SOD1 residues might be expected to have similar effects to mutations, but few modifications have been identified. Here we show, using SOD1 isolated from human erythrocytes, that human SOD1 is phosphorylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
166
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(173 citation statements)
references
References 37 publications
4
166
1
Order By: Relevance
“…SOD1 is responsible for destroying free superoxide radicals in the body [14]. Our data suggested that down-regulation of SOD1 in patients with varicocele and abnormal spermogram can elevate DNA fragmentation and apoptosis, but after varicocelectomy, SOD1 activity increases and it can be resulted in improving DNA damage.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…SOD1 is responsible for destroying free superoxide radicals in the body [14]. Our data suggested that down-regulation of SOD1 in patients with varicocele and abnormal spermogram can elevate DNA fragmentation and apoptosis, but after varicocelectomy, SOD1 activity increases and it can be resulted in improving DNA damage.…”
Section: Discussionmentioning
confidence: 72%
“…Our data suggested that down-regulation of SOD1 in patients with varicocele and abnormal spermogram can elevate DNA fragmentation and apoptosis, but after varicocelectomy, SOD1 activity increases and it can be resulted in improving DNA damage. Several studies have demonstrated that the total seminal plasma antioxidant levels in patients with varicocele are decreased and DNA damage in these patients was increased [12][13][14][15][16][17][18]. Moreover, some studies have shown that varicocelectomy can improve DNA fragmentation and total antioxidant capacity [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…For determination of surface-accessible sites in the SOD1 trimer in limited proteolysis studies, we isolated and purified SOD1 from human erythrocytes, as previously described (26). To generate SOD1 mutants for aggregation time courses using SEC, and WT SOD1 for comparison of comparable species, we performed cloning, expression, and purification of human recombinant SOD1 in Saccharomyces cerevisiae as described elsewhere (15,26,38). We determined the concentration of purified SOD1 species by measuring the A at 280 nm with an extinction coefficient of 10,800 M −1 ·cm −1 .…”
Section: Methodsmentioning
confidence: 99%
“…We reconstructed the four-bead centroid structure obtained from the DMD REX simulations described above to an all-atom model (29) and performed structural minimization using Chiron (50) to remove clashes introduced by reconstruction. To equilibrate our structure in a physical force field, we first performed low-temperature (below the melting transition) allatom REX simulations using 26 We selected the ideal number of replicas and spread of replica temperatures such that exchange of replicas occurs with an acceptance rate between 0.2 and 0.7, with exchange attempted every 1,000 time steps. We performed simulations for 10 6 time steps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation